El programa comunista : organo del Partido Comunista Internacional
For suppl. see: El proletario (ZK 40680). - Engl. ed.: Communist program (ZO 40138). - French ed.: Programme communiste (ZO 40488). - Germ.ed.: Kommunistisches Programm (ZK 40450). - Ital.ed.: Programma communista (ZF 40239).